2021
DOI: 10.1111/cas.15195
|View full text |Cite
|
Sign up to set email alerts
|

Circulating naïve and effector memory T cells correlate with prognosis in head and neck squamous cell carcinoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Nevertheless, our study suggests that without high-dose IL-2 intravenous injection, the progression of T cell exhaustion is slowed down, thus contributing to the long persistence of TILs. In addition, proportions of circulating CD8 + T cells in the peripheral circulation were an independent prognostic factor in patients with head and neck squamous cell carcinoma[ 31 ]. Consistent with the findings of previous studies, our results showed that CD8 + /CD4 + T cell ratio increased continuously post-infusion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our study suggests that without high-dose IL-2 intravenous injection, the progression of T cell exhaustion is slowed down, thus contributing to the long persistence of TILs. In addition, proportions of circulating CD8 + T cells in the peripheral circulation were an independent prognostic factor in patients with head and neck squamous cell carcinoma[ 31 ]. Consistent with the findings of previous studies, our results showed that CD8 + /CD4 + T cell ratio increased continuously post-infusion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…HNSCC is typically rich in CD8 T cell infiltrate but shows poor outcomes [ 68 ] and in HNSCC carcinogenesis, a population shift from naïve to memory T cell subtype has been noted [ 69 ], aligned with the finding of relative memory CD8 T cell enrichment in the high AMPHO group. CD8 T cell activation is associated with improved prognosis after the recurrence of HNSCC [ 70 , 71 ]. Of note, CD8 activation marker CD38 positive CD8 T cells have been associated with worse prognosis in HNSCC but also response to PD1 blockade [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 50 have mainly focused on infectious diseases such as tuberculosis and viruses. Recently, it has been reported 51 that Tem cells have great potential in tumor immunotherapy and prognosis. Takahashi et al 51 reported that the Tem high infiltration group was predicted to have longer OS among patients with head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported 51 that Tem cells have great potential in tumor immunotherapy and prognosis. Takahashi et al 51 reported that the Tem high infiltration group was predicted to have longer OS among patients with head and neck squamous cell carcinoma. Consistently, we found that Tem cells were associated with the prognosis of patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%